Semi-selective fatty acyl reductases from four heliothine moths influence the specific pheromone composition. - Asa K Hagström (Public Library of Science (PLoS), 2012)
Background Sex pheromones are essential in moth mate communication. Information on pheromone biosynthetic genes and enzymes is needed to comprehend the mechanisms that contribute to specificity of pheromone signals. Most heliothine moths use sex pheromones with (Z)-11-hexadecenal as the major component in combination with minor fatty aldehydes and alcohols. In this study we focus on four closely related species, Heliothis virescens, Heliothis subflexa, Helicoverpa armigera and Helicoverpa assulta, which use (Z)-11-hexadecenal, (Z)-9-tetradecanal, and (Z)-9-hexadecenal in different ratios in their pheromone blend. The components are produced from saturated fatty acid precursors by desaturation, β-oxidation, reduction and oxidation. Results We analyzed the composition of fatty acyl pheromone precursors and correlated it to the pheromone composition. Next, we investigated whether the downstream fatty-acyl reduction step modulates the ratio of alcohol intermediates before the final oxidation step. By isolating and functionally characterizing the Fatty Acyl Reductase (pgFAR) from each species we found that the pgFARs were active on a broad set of C8 to C16 fatty acyl substrates including the key pheromone precursors, Z9-14, Z9-16 and Z11-16:acyls. When presenting the three precursors in equal ratios to yeast cultures expressing any of the four pgFARs, all reduced (Z)-9-tetradecenoate preferentially over (Z)-11-hexadecenoate, and the latter over (Z)-9-hexadecenoate. Finally, when manipulating the precursor ratios in vitro, we found that the pgFARs display small differences in the biochemical activity on various substrates. Conclusions We conclude that a pgFAR with broad specificity is involved in heliothine moth pheromone biosynthesis, functioning as a semi-selective funnel that produces species-specific alcohol product ratios depending on the fatty-acyl precursor ratio in the pheromone gland. This study further supports the key role of these in pheromone biosynthesis and emphasizes the interplay between the pheromone fatty acyl precursors and the Lepidoptera specific pgFARs in shaping the pheromone composition.